Definitive‐intent intensity‐modulated radiation therapy provides similar outcomes to those previously published for definitive‐intent three‐dimensional conformal radiation therapy in dogs with primary brain tumors: A multi‐institutional retrospective study. Issue 4 (1st May 2020) - Van Asselt, Nathaniel; Christensen, Neil; Meier, Valeria; Rohrer Bley, Carla; Laliberte, Sarah; Poirier, Valerie J.; Desai, Noopur; Chen, Yi; Turek, Michelle
Abstract: Radiotherapy with or without surgery is a common choice for brain tumors in dogs. Although numerous studies have evaluated use of three‐dimensional conformal radiotherapy, reports of definitive‐intent, IMRT for canine intracranial tumors are lacking. Intensity‐modulated radiation therapy has the benefit of decreasing dose to nearby organs at risk and may aid in reducing toxicity. However, increasing dose conformity with IMRT calls for accurate target delineation and daily patient positioning, in order to decrease the risk of a geographic miss. To determine survival outcome and toxicity, we performed a multi‐institutional retrospective observational study evaluating dogs with brain tumors treated with IMRT. Fifty‐two dogs treated with fractionated, definitive‐intent IMRT at four academic radiotherapy facilities were included. All dogs presented with neurologic signs and were diagnosed via MRI. Presumed radiological diagnoses included 37 meningiomas, 12 gliomas, and one peripheral nerve sheath tumor. One dog had two presumed meningiomas and one dog had either a glioma or meningioma. All dogs were treated in the macroscopic disease setting and were prescribed a total dose of 45‐50 Gy (2.25‐2.5 Gy per fraction in 18‐20 daily fractions). Median survival time for all patients, including seven cases treated with a second course of therapy was 18.1 months (95% confidence of interval 12.3‐26.6 months). As previously described for brain tumors, increasing severity of neurologic signs at diagnosis was associated with a worse outcome. Intensity‐modulated radiation therapy was well tolerated with few reported acute, acute delayed, or late side effects.